2018
DOI: 10.1111/oik.05670
|View full text |Cite
|
Sign up to set email alerts
|

Motifs in bipartite ecological networks: uncovering indirect interactions

Abstract: Indirect interactions play an essential role in governing population, community and coevolutionary dynamics across a diverse range of ecological communities. Such communities are widely represented as bipartite networks: graphs depicting interactions between two groups of species, such as plants and pollinators or hosts and parasites. For over thirty years, studies have used indices, such as connectance and species degree, to characterise the structure of these networks and the roles of their constituent speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
180
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 82 publications
(181 citation statements)
references
References 99 publications
(216 reference statements)
0
180
0
1
Order By: Relevance
“…, Olito and Fox , Simmons et al. ). Studies testing mechanisms for interaction turnover rarely validate that their proposed mechanisms are correctly predicting observed interactions, and thus, the observed similarity between empirical and predictive models of interaction turnover may be arising for the wrong reasons (Olito and Fox ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…, Olito and Fox , Simmons et al. ). Studies testing mechanisms for interaction turnover rarely validate that their proposed mechanisms are correctly predicting observed interactions, and thus, the observed similarity between empirical and predictive models of interaction turnover may be arising for the wrong reasons (Olito and Fox ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Simmons et al. () used a motif approach and demonstrated that it was significantly more effective at describing network structure than traditional network metrics. Further, when Baker et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations